1981
DOI: 10.1055/s-2007-1019190
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Insulin Release Periodicity from Individual Islets of Obese Zucker Rats

Abstract: Utilizing individual islets of Langerhans, Bessman, Beigelman and have demonstrated a pulsatile periodicity of insulin release. More recent data, have correlated this pulsatile pattern of insulin release with bursts of electrical activity in single microdissected islets exposed to glucose (Atwater, Rojas and Scott 1979;Beigelman and Ribalet 1980). Materials and MethodsIslets from obese and lean Zucker rats were isolated by the collagenase method of Shibata, Ludvigsen, Naber, McDaniel and Lacy (1976). Individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Intrahepatic transplanted islets become vascularized within 7 d of transplantation (12). The present data therefore appear to lend additional argument against the hypothesis that coordinate pulsatile insulin secretion in vivo is due to entrainment of islets by either oscillations in circulating glucose (8) or an intrinsic metabolic cycle present in pancreatic islets (26). It has been suggested that coordinate secretory burst activity is achieved through the intrapancreatic nerve network (10,27).…”
Section: Discussionmentioning
confidence: 48%
“…Intrahepatic transplanted islets become vascularized within 7 d of transplantation (12). The present data therefore appear to lend additional argument against the hypothesis that coordinate pulsatile insulin secretion in vivo is due to entrainment of islets by either oscillations in circulating glucose (8) or an intrinsic metabolic cycle present in pancreatic islets (26). It has been suggested that coordinate secretory burst activity is achieved through the intrapancreatic nerve network (10,27).…”
Section: Discussionmentioning
confidence: 48%
“…In addition, direct sampling from the portal vein in vivo supports the contention that serum insulin oscillations are primarily a secretory phenomenon (3). Studies published in single isolated rat (11,12) and mouse (13) islets have demonstrated high-frequency insulin secretory cycles, but whether these bear any relationship to the fluctuations observed in vivo is unclear. It is not clear, however, whether the pacemaker for oscillatory insulin secretion is within the pancreatic nervous system or whether the islets have an intrinsic pulsatile rhythm that is coordinated by the extensive neurogenic connections of the pancreas.…”
mentioning
confidence: 85%
“…However, the net contribution of the secretory bursts is important, because the presence of concentration oscillations does not exclude the dominance of a time-invariant (basal) release pattern. Furthermore, the relation between the in vivo observed secretory bursts and the in vitro observed pulsatile release from the isolated pancreas [9,10,101] and the isolated peri-perfused islets [102,103], as well as episodic beta-cell depolarization [104±106], beta-cell glycolysis [105,107], and beta-cell increase in calcium remains to be established [104, 105, 108±111]. The coupling of cyclic metabolism to pulsatile in vitro release has been addressed in an excellent review by Tornheim [112].…”
Section: Contribution Of Pulsatile Insulin Release To the Overall Insmentioning
confidence: 99%